Trends and innovations in ocean mesoscale eddy studies via satellite observation: a bibliometric review - Xu, Fan; Wen, Zhiqiang; Wang, Huimin; Li, Tong; Song, Xiufang; Peng, Hao (Frontiers in Marine Science, 2025)
Ocean mesoscale eddies play a crucial role in global ocean circulation, heat transport, and biogeochemical processes. Satellite altimetry has become a foundation in observing and analyzing these dynamic phenomena, offering high-resolution, global coverage of sea level anomalies. This bibliometric review investigates the trends and innovations in mesoscale eddy research using satellite altimetry data over the past decades. Based on Web of Science, VOSviewer, and CiteSpace, we analyze publication growth, geographical and institutional contributions, keyword co-occurrence, and citation networks. Key innovations such as advanced data assimilation, multi-satellite collaboration, and integration with machine learning models are highlighted. Finally, we discuss future opportunities of next-generation altimetry missions like SWOT for mesoscale eddy dynamics. This review serves as a comprehensive guide for researchers exploring mesoscale eddies and satellite-based ocean observations.